Dìntanulyķ bìlìmniṇ šeteldìk ta̋žìribesì (N.A. Rubakin men N. Smart eṇbekterìn taldau negìzìnde) - Kulsariyeva, A. T. (Chabaršy. Dintanu serijasy, 2019)
The article discusses the theories and ideas of foreign religious scholars, their importance for the study of domestic religious education is quite a new scientific direction in our country. The article analyzes the religious thought of Western, Russian religious scholars, the relevance of the problems studied in the past century in the context of Kazakhstan's realities, recommended scientific results on this issue based on the analysis "Among the Books" by N.А. Rubakin and N. Smart's works. In the article, the means of analyzing the work of these scholars are given to one degree or another by directions for researchers in the field of religious education. In the heyday of the virtual world Rubakin's work "Among the books" is not yet so widely spread, including his ideas about religious studies as a science. The main methodological support separating religious knowledge from religious knowledge is objectivity and ideological neutrality. At the time of defining religions and religious associations, adhering to the principles of science, religious education does not attempt to establish any particular opinions about a particular religion, but aims to preserve the principles of secularism.